2020
DOI: 10.1016/j.jtcme.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of piperine in ischemia-reperfusion induced acute kidney injury through inhibition of inflammation and oxidative stress

Abstract: Background and aim Renal ischemia-reperfusion is associated with inflammation and oxidative stress. As a major compound in black pepper, piperine has anti-inflammatory and anti-oxidative properties. In present study, the protective effects of oral administration of piperine in renal ischemia-reperfusion (IR) induced acute kidney injuries (AKI) were investigated. Experimental procedure Male Wistar rats received piperine (10 or 20 mg/kg.bw) or vehicle for 10 days. The art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…Coronavirus in the kidney can cause AKI and other disturbances in kidney function [23] , [24] . Acute kidney injury is a condition which blood urea and creatinine concentrations increase via the retention of nitrogenous wastes, decrease GFR, as well as extracellular fluid volume and electrolyte homeostasis derangement [25] , [26] , [27] . Although AKI is an uncommon feature of SARS-CoV-2, it is known to be a fatal complication with early reports indicating 3 to 9% prevalence of AKI in the patients with COVID-19 [28] .…”
Section: Epidemiology and Pathophysiology Of Covid-19 Induced Acute Kidney Injurymentioning
confidence: 99%
“…Coronavirus in the kidney can cause AKI and other disturbances in kidney function [23] , [24] . Acute kidney injury is a condition which blood urea and creatinine concentrations increase via the retention of nitrogenous wastes, decrease GFR, as well as extracellular fluid volume and electrolyte homeostasis derangement [25] , [26] , [27] . Although AKI is an uncommon feature of SARS-CoV-2, it is known to be a fatal complication with early reports indicating 3 to 9% prevalence of AKI in the patients with COVID-19 [28] .…”
Section: Epidemiology and Pathophysiology Of Covid-19 Induced Acute Kidney Injurymentioning
confidence: 99%
“…In this context, easy availability and accessibility to plant-derived therapies are of prime importance. Plants represent a rich source of phytochemicals which have a high potential to act both as exogenous antioxidant and anti-inflammatory agents, as evidenced by many studies [ 27 , 100 104 ]. Therefore, treating I/R-induced AKI with plant-derived extracts and compounds is the most practical approach.…”
Section: Resultsmentioning
confidence: 99%
“…The renal I/R injury induced-AKI causes necrosis, apoptosis, hemorrhages, vascular congestion, inflammatory cell infiltration, cellular edema, and other degenerative changes in kidney tissues [ 27 , 104 , 131 , 148 ]. Plant-derived extracts and compounds have shown marked effects on kidney tissues, almost all the plants effectively lowered the total renal histopathological scores ( Table 1 ).…”
Section: Effects On Biomarkers and Renal Tissuesmentioning
confidence: 99%
“… Chloroform fruit extract and ursolic acid showed potent hepatoprotective activity against hepatocarcinogenesis on MCF-7 and HepG2 cell line and restored various biochemical parameters Liver related problem Ali et al, 2019 Methanol extract of stem bark reduced the production of pro-inflammatory cytokine IL-6, TNF-α in LPS-stimulated RAW 264.7 macrophages. It also reduced in-vivo neutrophils, macrophages, nitric oxide and inducible nitric oxide synthase levels, inflammatory cells infiltration and monocyte chemoattractant protein-1 in lipopolysaccharide treated mice Lung related complications Lee et al, 2018 Piperaceae Piper longum L. Piperine improved plasma concentrations of creatinine, urea-nitrogen, expression of pro-inflammatory factors, oxidative stress and renal histopathological injuries in ischemia-reperfusion rat Kidney complications Mohammadi et al, 2019 Piperine potentially reduced activation of microglia and blocked release of proinflammatory cytokines thus, protected dopaminergic neurons damage Parkinsonism He et al, 2016 Methanol extract of fruits inhibited monoamine oxidase activity and increased monoamine neurotransmitters levels in β-amyloid treated rat Mental Problem Hritcu et al, 2015 Alcohol fruit extract inhibited bronchospasm and blocked the release of histamine in in-vitro guinea-pig ileum preparation and histamine treated guinea-pig Lung related complications Kaushik et al, 2012 Piperine showed negative inotropic and negative chronotropic effect by blocking the action of adrenalin in isolated frog heart Cardiac complications Lokhande et al, 2006 Piperine improved glutathione and peroxide level in the liver cell in tert-butyl hydroperoxide and carbon tetrachloride treated mice Liver related problem Koul and Kapil, 1993 Piper nigrum L. Essential oil from fruits showed anxiolytic and antidepressant activity and improved behavioural changes in depressed mice model Mental Problem Ghosh et al, 2021 Ethanol extract of seed showed nephroprotective activity by improving serum biochemical parameter and histopathological changes in para-amino salicylic acid treated rats Kidney complications …”
Section: Herbal Formulae From Different Traditional Systems Of Medicinementioning
confidence: 99%